2021
DOI: 10.21037/apm-21-219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peer support on improving self-management ability in peritoneal dialysis patients—a randomized controlled trial

Abstract: Background: Peritoneal dialysis (PD) is an ideal method for the treatment of chronic kidney disease.Its survival rate and quality of life depend on the quality of dialysis. The quality of dialysis depends on the compliance of patients with drugs and dialysis treatment, the choice of diet, the detection of complications and the monitoring and management of the disease. Therefore, the self-management of PD patients is particularly important. This study explored the role of peer support in improving the self-mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The study has confirmed that peer support can effectively improve the self-management ability of PD patients. 23 It is fascinating to note that A couple of young people in the WeChat group have met - fallen in love - and are married, encouraging and supporting each other in the face of life and illness. WeChat can be an effective tool for the management of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study has confirmed that peer support can effectively improve the self-management ability of PD patients. 23 It is fascinating to note that A couple of young people in the WeChat group have met - fallen in love - and are married, encouraging and supporting each other in the face of life and illness. WeChat can be an effective tool for the management of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in China, the studies on the self-management ability of PD patients primarily focused on the developed areas of eastern China. 22 , 23 However, the self-management of PD patients in Xinjiang Northwest China is rarely reported. Xinjiang covers about one-sixth of China’s total land area.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-dimensional program including novel, scalable strategies that can provide needed social support to improve patients’ self-efficacy and self-management is critically needed. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Li et al, 2014), mobile applications to enhance quality of life (K. Singh et al, 2019a;T. Singh et al, 2019b), and peer support (Chen et al, 2021). To date, there has been a lack of evidence that focuses on improving self-management for patients receiving PD.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, previous studies on self‐management in patients receiving PD have examined home visits focusing on reduced rates of peritonitis and hospital admission (Martino et al, 2014), exercise intervention with a focus on reduced blood glucose (Shahgholian et al, 2015), posttreatment phone counseling for enhancing quality of life (J. Li et al, 2014), mobile applications to enhance quality of life (K. Singh et al, 2019a; T. Singh et al, 2019b), and peer support (Chen et al, 2021). To date, there has been a lack of evidence that focuses on improving self‐management for patients receiving PD.…”
Section: Introductionmentioning
confidence: 99%